Regional-based potential assessment for solar photovoltaic generation in northern part of Nigeria using satellite imagery data - Mohammed K. Salihu; Ali Danladi; D. W. Medugu (Bulletin of the National Research Centre)
Abstract Background This research used satellite imagery data to conduct a regional-based potential assessment for solar photovoltaic generating in the northern section of Nigeria. The mean annual global solar radiation from satellite image data was calculated and to compare it with meteorological data, the study area’s temperature was ascertained using satellite images. ArcGIS was also used to determine the appropriateness axis for the development of solar photovoltaic stations in the northern part of Nigeria. Photovoltaic technology was utilized to transform the calculated amounts of solar radiation on a global scale into potential electrical energy. Results The findings show that the northeast region has the highest annual mean value of global solar radiation (2179.5 kilowatts-hours/square-meter/Year), followed by the northwest region (2137.5 kilowatts-hours/square-meter/Year), and the north central region (1909.6 kilowatts-hours/square-meter/Year). The influence of global solar radiation also caused an increase in temperature. With an area value of 174,886 kilometer-square, the northeast region has the greatest suited axis for the development of solar PV stations, followed by the north central region (145,187 kilometer-square) and the northwest region (127,470 kilometer-square). The greatest photovoltaic technology, single-crystalline silicon (500.5 Gigawatts), is followed by multi-crystalline silicon (462.5 Gigawatts), cadmium-telluride (362.7 Gigawatts), and amorphous-silicon (81.10202.8 Gigawatts), which has the lowest value. Conclusions It is discovered that Nigeria’s north receives more solar radiation from the sun than the rest of the country, and that the region has the ability to produce enough electricity to power the entire nation.